Syncing with Families: Using Technology in Early Childhood Programs - Burris, Jade (American Journal of Education and Learning, 2019)
Family engagement in education has been proven to positively support children’s learning. For many children, their first school experience is now in an out-of-home child care facility where they begin care between six weeks and six years old prior to attending kindergarten. Families of young children depend on child care programs now more than ever, and the importance of family engagement is even more apparent as children spend long hours in the care of others. Innovations in tools and devices, especially the addition of the smartphone, have allowed teachers to leverage technology to meet the individual needs of each family, bridging the gap between school and home like never before. This study, using Epstein’s Framework for Six Types of Parental Involvement examined how early childhood programs use technology to engage families. Based on data from child care directors’ survey responses, three trends emerged: 1) programs used technology mostly to communicate with families, 2) programs leveraged real-time technology to communicate with all family members, and 3) programs still find technology challenging. These findings have implications for teacher preparation programs as well as in-service professional development systems related to the use and application of technology to engage families.